2009
DOI: 10.1016/j.virol.2008.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of the human T-cell leukemia virus type 1 Tax oncoprotein by p300 promotes activation of the NF-κB pathway

Abstract: The oncogenic potential of the HTLV-1 Tax protein involves activation of the NF-κB pathway, which depends on Tax phosphorylation, ubiquitination and sumoylation. We demonstrate that the nuclei of Tax-expressing cells, including HTLV-1 transformed T-lymphocytes, contain a pool of Tax molecules acetylated on lysine residue at amino acid position 346 by the transcriptional coactivator p300. Phosphorylation of Tax on serine residues 300/301 was a prerequisite for Tax localization in the nucleus and correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 67 publications
(80 reference statements)
3
57
0
Order By: Relevance
“…Lodewick et al recently showed that both Tax1 and Tax2 are acetylated (65). Since acetylation occurs on lysine residues, it is expected that Tax2-K0 would be defective for acetylation, which might in turn impact its transcriptional activity.…”
Section: Resultsmentioning
confidence: 99%
“…Lodewick et al recently showed that both Tax1 and Tax2 are acetylated (65). Since acetylation occurs on lysine residues, it is expected that Tax2-K0 would be defective for acetylation, which might in turn impact its transcriptional activity.…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitination, sumoylation, acetylation, and phosphorylation of Tax have been shown to influence its transcriptional function (5,9,22,23,25,28,34,35,40). Tax ubiquitination has been reported to be required for its activation of NF-B, and it has been found that the Tax-polyubiquitin chains are predominantly K63 linked (40).…”
Section: Resultsmentioning
confidence: 99%
“…10,11 Posttranslational modification of proteins regulates protein functions by modifying their subcellular localization, stability, and/or network of interaction. We and others have described different forms of Tax posttranslational modifications including phosphorylation, 12,13 acetylation, 14 ubiquitylation, and small ubiquitin-like modifier (SUMO)ylation, 15,16 all of which are implicated in Tax-mediated activation of gene expression. Indeed, we showed that Tax is differentially ubiquitylated by either K-48 ubiquitin chains leading to Tax degradation by the proteasome or by K-63 ubiquitin chains that mediates IKK recruitment to the centrosome and IKK activation.…”
Section: Introductionmentioning
confidence: 99%